2007
DOI: 10.1016/j.juro.2007.03.115
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Factors on Prognosis of Patients With pT3 Upper Urinary Tract Transitional Cell Carcinoma

Abstract: The present study demonstrated that patients with pT3 disease with superficial parenchymal invasion should be considered to have lower stage disease, and that vascular involvement is the only independent prognostic factor for patients with pT3 disease for disease-free and recurrence-free survival. Systemic adjuvant therapy should be recommended for patients with pT3 disease with vascular involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 19 publications
2
30
1
Order By: Relevance
“…Although several studies have identified LVI as a poor prognostic feature, only a few have controlled for possible confounding factors by using multivariate analyses. 4,8,12,23,24 In agreement with several single-center reports, our multiinstitutional study revealed that 25% of patients undergoing RNU for UTUC had histologically identifiable LVI. As previously reported in several cystectomy and RNU series, LVI was associated with advanced stage, grade, and LN status.…”
Section: 46supporting
confidence: 90%
See 2 more Smart Citations
“…Although several studies have identified LVI as a poor prognostic feature, only a few have controlled for possible confounding factors by using multivariate analyses. 4,8,12,23,24 In agreement with several single-center reports, our multiinstitutional study revealed that 25% of patients undergoing RNU for UTUC had histologically identifiable LVI. As previously reported in several cystectomy and RNU series, LVI was associated with advanced stage, grade, and LN status.…”
Section: 46supporting
confidence: 90%
“…As previously reported in several cystectomy and RNU series, LVI was associated with advanced stage, grade, and LN status. 4,8,9,12,[23][24][25][26] Importantly, we found that LVI was also an independent predictor of relapse and death from UTUC. Several investigators have reported that the tumor growth pattern, as defined by Jimenez at al is an independent predictor of oncologic outcome in patients treated with radical cystectomy for urothelial carcinoma of the urinary bladder.…”
Section: 46supporting
confidence: 51%
See 1 more Smart Citation
“…One retrospective study of patients after nephroureterectomy with a sample size <100 was included by author consensus because of its large sample of pT3 tumours. 27 No studies were excluded for major …”
Section: Resultsmentioning
confidence: 99%
“…10,18,20,23,25 Among 72 patients with pT3 tumours and a median follow-up of 26.5 months, recurrences of the retroperitoneum/pelvis and contralateral upper tract were observed in 7% and 3%, respectively. 27 Distant metastases occurred following nephroureterectomy in 16.4% of patients (8%-28%; 46.8 months). The reported sites of metastases included retroperitoneal lymph nodes in 5.2% (0-9.8%; 49.0 months), lung in 4.8% (0-8%; 50.2 months), bone in 4.1% (0-9%; 50.2 months) and liver in 3.7% (0-5%; 50.2 months).…”
Section: Extravesical Recurrencesmentioning
confidence: 99%